Komoditas Yang Mempengaruhi Surplus Perdagangan Indonesia Mulai 2024 Sampai Dengan Semester Pertama 2025 - Taufik Hidayadi; Mohammad Zuhdi (MIZANIA: Jurnal Ekonomi Dan Akuntansi, 2025)
Indonesia's trade surplus is expected to remain in the first half of 2025, with positive performance from exports of leading commodities. This study identifies the main commodities contributing to the surplus and the factors influencing it. Based on data from the Central Statistics Agency (BPS) and the Ministry of Trade, crude palm oil (CPO), coal, iron, and steel are the commodities with the largest contributions. Global supply chains and demand from key trading partners drive export performance. To increase competitiveness and strengthen economic resilience, this study recommends industrial diversification and downstreaming.